Mechanical response comparison in an implant overdenture retained by ball attachments on conventional regular and mini dental implants: a finite element analysis. Issue 8 (10th June 2016) - Chang, Shih-Hao; Huang, Shiang-Rung; Huang, Shao-Fu; Lin, Chun-Li
Abstract: This study investigates the bone/implant mechanical responses in an implant overdenture retained by ball attachments on two conventional regular dental implants (RDI) and four mini dental implants (MDI) using finite element (FE) analysis. Two FE models of overdentures retained by RDIs and MDIs for a mandibular edentulous patient with validation within 6% variation errors were constructed by integrating CT images and CAD system. Bone grafting resulted in 2 mm thickness at the buccal side constructed for the RDIs-supported model to mimic the bone augmentation condition for the atrophic alveolar ridge. Nonlinear hyperelastic material and frictional contact element were used to simulate characteristic of the ball attachment-retained overdentures. The results showed that a denture supported by MDIs presented higher surrounding bone strains than those supported by RDIs under different load conditions. Maximum bone micro strains were up to 6437/2987 and 13323/5856 for MDIs/RDIs under single centric and lateral contacts, respectively. Corresponding values were 4429/2579 and 9557/5774 under multi- centric and lateral contacts, respectively. Bone micro strains increased 2.06 and 1.96-folds under single contact, 2.16 and 2.24-folds under multiple contacts for MDIs and RDIs when lateral to axial loads were compared. The maximum RDIs and MDIs implant stresses in all simulated cases were found by far lower than their yield strength. Overdentures retained using ball attachments on MDIs in poor edentulous bone structure increase the surrounding bone strain over the critical value, thereby damaging the bone when compared to the RDIs. Eliminating the occlusal single contact and oblique load of an implant-retained overdenture reduces the risk for failure.